ANALISIS PERSEDIAAN KOPI DALAM MEMENUHIPERMINTAAN PASAR (Studi kasus di Kelompok Tani Rahayu Kecamatan Pangalengan Kabupaten Bandung ) - Wini Fetia Wardhiani (Paspalum: Jurnal Ilmiah Pertanian, 2015)
An analysis of the coffee supply to meet market demand, a case study in the "FarmersRahayu" Pangalengan, Bandung regency. Rahayu Farmer Group is one of the most advanced coffee producer compared with other farmer groups in the village Margamulya. However, Rahayu Farmer Group have yet to implement a particular supply model for managing a supply of coffee. Thus, Farmers Group Rahayu not know how efficient and effective inventory management coffee they have done. Therefore, the authors feel compelled to discuss more about the study of coffee in the inventory management Rahayu Farmer Group. The purpose of this research is to know about the inventory management is done by Farmers Group Rahayu and coffee inventory management according to the model of EOQ (Economic Order Quantity). Model Research conducted in this study is a case study. Data collection techniques used were observation, interview, and literature study.The results prove that inventory management is done by Farmers Group Rahayu has not been effective and efficient. This can be evidenced through a comparison between the inventory model used by the actual conditions that occur in the company. EOQ inventory model has a total cost of 17.43% lower. EOQ model with safety stock have 5% lower total cost of supply.